2015
DOI: 10.1007/s10072-015-2182-5
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy of erythropoietin (EPO) treatment in traumatic spinal cord injury: a preliminary randomized comparative trial vs. methylprednisolone (MP)

Abstract: The only available treatment of traumatic spinal cord injury (TSCI) is high-dose methylprednisolone (MP) administered acutely after injury. However, as the efficacy of MP is controversial, we assessed the superiority of erythropoietin (EPO) versus MP in improving clinical outcome of acute TSCI. Patients aged 18 to 65 years after C5-T12 injury, and grade A or B of the ASIA Impairment Scale (AIS), admitted within 8 h, hemodynamically stable, were randomized to MP according to the NASCIS III protocol or EPO iv (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In this trial, the effect of EPO treatment was compared with high-dose methylprednisolone treatment. EPO had higher efficacy and fewer side effects than methylprednisolone, indicating a therapeutic effect for acute SCI patients [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this trial, the effect of EPO treatment was compared with high-dose methylprednisolone treatment. EPO had higher efficacy and fewer side effects than methylprednisolone, indicating a therapeutic effect for acute SCI patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Those papers reported its effect of neuroprotection, angiogenesis, and anti-apoptosis in the brain and spinal cord [18, 24]. Recently, recombinant human EPO (rhEPO) was preliminarily used in a randomized clinical trial of acute SCI, and results indicated the possibility of treating acute SCI with EPO [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fundamental myeloprotective role of EPO, these findings also demonstrated an anti‐oxidative effect of EPO at the site of nerve injury which is consistent with the direct role of EPO against oxidative stress (Maiese et al, ). Given EPO’s widespread and frequent use to treat anemia in humans and its favorable side effect profile (Itri, ; Straus, ), early clinical trials have already begun investigating EPO’s therapeutic potential treating human peripheral nerve trauma associated with joint replacement surgery (Bernstein et al, ; Costa et al, ). It is also noteworthy that clinical use of EPO is not without problems, in particular the route of administration and the potent side effect profile.…”
Section: Erythropoietinmentioning
confidence: 99%
“…Ten paraparetic patients with malignant extradural spinal cord compression (MESCC) received 1500 IU kg −1 EPO by chemotherapy infusion pump over 30 min and showed improved motor function and shorter recovery time, including functional class and ambulation 244. Additionally, Costa et al found that intravenous administration of EPO resulted in a meaningful clinical improvement in ASIA Impairment Scale scores compared with MP treatment 245. Meanwhile, the combination of EPO and MP has been confirmed in clinical trials to be beneficial for SCI treatment 246.…”
Section: Clinical Studiesmentioning
confidence: 99%